The Case for Creating a National DNA Repository of Biological Samples in the Russian Federation - I. V. Kornienko; T. G. Faleeva; V. S. Rakuts; I. N. Ivanov; Yu. S. Sidorenko (Теория и практика судебной экспертизы)
The article examines the relevance of creating a national repository of biological samples collected from Russian citizens. International practices in the introduction and application of proactive DNA-based human identification are analyzed. Information is provided about existing molecular genetic databanks, including one of the largest in the world – the UK National DNA Database containing over 6 million genetic profiles. Availability of reference samples for comparison helps in the identification of evidence found at the scene and thus contributes to effective crime detection. Authors point out the lack of uniform standards for human DNA marker analysis both in Russia and abroad, which significantly complicates DNA identification of biological material. Once a national databank of biological samples is established, the absence of a universally recognized DNA profiling system would be rendered irrelevant. Successful achievement of this objective relies on the use of the most effective and affordable method for collection and long-term storage of genetic material in dry form, i.e. collection paper cards (DNA cards).